When you do not know ho you are! - Roy, Anirban; Mohapatra, Animesh Kumar (SCHOOL SCIENCE, 2015)
The entire class fell silent as the teacher, Mrs Baldwin, marched across the room. Mrs Baldwin wearily shouted, “Kim Noble, Stand up! I said you stand up!”. She shouted grabbing the arm of five-year-old Kim Noble. Mrs Baldwin questioned, “What did you do that for?”. The dress she was wearing was covered in splurges of black paint. Sitting in her drawing room, Kim Noble, now 51, recalls, “Of course, the teacher was exasperated when I denied doing it because she had seen me smear it over myself.” But till date, Kim Noble, who now has a daughter, refuses to accept that she had blurred her dress with black paint. But as far as I was concerned, it was somebody else who did it, she says. What Kim could not have known then was that she was suffering from a rare condition called ‘Dissociative Identity Disorder’ (DID)— colloquially known as ‘split personality disorder’— and that over the next four decades her mind would regularly switch from one character to another without warning. Deborah Bray Haddock in her book The Dissociative Identity Disorder Sourcebook, says, “Dissociative Identity Disorder, in short DID, is about survival! As more people begin to appreciate this concept, individuals with DID will start to feel less as though they have to hide in shame. DID develops as a response to extreme trauma that occurs at an early age and usually over an extended period of time.”